Assessment of the protein interaction between coagulation factor XII and corn trypsin inhibitor by molecular docking and biochemical validation. (9th August 2017) - Hamad, B. K.; Pathak, M.; Manna, R.; Fischer, P. M.; Emsley, J.; Dekker, L. V.
Abstract : Essentials Corn Trypsin Inhibitor (CTI) is a selective inhibitor of coagulation Factor XII (FXII). Molecular modelling of the CTI‐FXIIa complex suggested a canonical inhibitor binding mode. Mutagenesis revealed the CTI inhibitory loop and helices α1 and α2 mediate the interaction. This confirms that CTI inhibits FXII in canonical fashion and validates the molecular model. Summary: Background: Corn trypsin inhibitor (CTI) has selectivity for the serine proteases coagulation factor XII and trypsin. CTI is in widespread use as a reagent that specifically inhibits the intrinsic pathway of blood coagulation but not the extrinsic pathway. Objectives: To investigate the molecular basis of FXII inhibition by CTI. Methods: We performed molecular docking of CTI, using its known crystal structure, with a model of the activated FXII (FXIIa) protease domain. The interaction model was verified by use of a panel of recombinant CTI variants tested for their ability to inhibit FXIIa enzymatic activity in a substrate cleavage assay. Results: The docking predicted that: (i) the CTI central inhibitory loop P1 Arg34 side chain forms a salt bridge with the FXIIa S1 pocket Asp189 side chain; (ii) Trp22 from CTI helix α1 interacts with the FXIIa S3 pocket; and (iii) Arg43 from CTI helix α2 forms a salt bridge with FXIIa H1 pocket Asp60A. CTI amino acid substitution R34A negated all inhibitory activity, whereas the G32W, L35A, W22A and R42A/R43A substitutions reduced activity by large degrees of 108‐fold, 41‐fold, 158‐fold, and 100‐fold, respectively; the R27A, W37A, W39A and R42A substitutions had no effect. Synthetic peptides spanning CTI residues 20–44 had inhibitory activity that was three‐fold to 4000‐fold less than that of full‐length CTI. Conclusions: The data confirm the validity of a canonical model of the FXIIa–CTI interaction, with helix α1 (Trp22), central inhibitory loop (Arg34) and helix α2 (Arg43) of CTI being required for effective binding by contacting the S1, S3 and H1 pockets of FXIIa, respectively.